THE EFFORTS TO INCREASE THE PERFORMANCE OF THE SAMAPTA POLICE PATROL UNIT OF THE TEGAL POLICE TO PREVENT VEHICLE THEFT IN TEGAL REGENCY - Alvernio Daffa Noya Noya (Police Studies Review, 2022)
The crime of vehicle theft is a crime of theft with a special object of motor vehicle. One of the districts in Central Java that contributes to this crime rate is Tegal Regency. Geographically, the location of Tegal Regency is considered easy for cross-region actors to arrive. One of the prevention efforts carried out is to carry out patrol activities. Based on the background and identification of the problem can be determined the formulation of existing problems, namely how the performance of the Samapta Police Patrol Unit of Tegal Police in preventing vehicle theft in order to realize safety and public order and what efforts are made to improve the performance of the Samapta Police Patrol Unit of Tegal Police in preventing vehicle theft. In this study, a qualitative approach was used with primary and secondary data sources at the Tegal Police Station, as well as previous thesis in the research library. The method used is descriptive analysis, with the data collection techniques used are interviews and document studies. The theories used in this research are management theory, swot analysis theory and competency theory, while the concepts used are patrol concepts, vehicle theft concepts, performance concepts. The conclusion in this study is that the implementation of patrol unit performance and optimization form of patrol unit performance has not been optimal because the number of vehicle theft that occurred until the 2021 data is still the first highest crime rate in Tegal Regency, so that the author provides problem solving solutions to problems and suggestions, namely the first is the need for improvements in terms of patrol implementation management, in terms of preparation to control. Second, eliminating cooperation in the implementation of patrols, especially in vulnerable areas, then there are variations in the route and timing of implementation in routine patrol activities, and then optimize dialogical patrols by conveying messages – safety and public order message to increase vigilance in the community, as well as efforts made by the leadership must be supported by the implementing element to realize safety and public order and prevent vehicle theft crimes that are higher than other criminalities.